2017
DOI: 10.1021/acs.energyfuels.7b00034
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Glycerol Transesterification with Propylene Carbonate to Glycerol Carbonate over a Solid Base Catalyst

Abstract: Glycerol transesterification using propylene carbonate (PC) to glycerol carbonate (GC) could be efficiently performed under solvent-free conditions using solid base as catalysts involving non-noble metal oxide in combination with hydrotalcites (HTs). Among all of the catalysts studied for transesterification, the best result was obtained over a calcium-doped hydrotalcite (Ca-HT) catalyst, giving 84% conversion of glycerol and almost complete GC selectivity. The crystal structure of HT was modified by incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…This trend in activity is ascribed to the stronger basicity of OH − compared to Cl − and I − [30] . The hydroxide ion can promote this reaction by abstracting a proton from glycerol, leading to the formation of a nucleophilic alkoxy ion, which facilitates the nucleophilic attack on the carbonyl group of propylene carbonate [33] . As a consequence, a carbonate intermediate ion is formed, which undergoes ring closure, yielding glycerol carbonate [33] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend in activity is ascribed to the stronger basicity of OH − compared to Cl − and I − [30] . The hydroxide ion can promote this reaction by abstracting a proton from glycerol, leading to the formation of a nucleophilic alkoxy ion, which facilitates the nucleophilic attack on the carbonyl group of propylene carbonate [33] . As a consequence, a carbonate intermediate ion is formed, which undergoes ring closure, yielding glycerol carbonate [33] .…”
Section: Resultsmentioning
confidence: 99%
“…MgO, CaO and MgO@ZIF‐8) [17,40–42] and hydrotalcites [43–45] . Based on these previous studies, the presence of a basic catalytic site is crucial to initiate this reaction by abstracting a proton from glycerol, which results in the formation of the glyceroxide ion, thus enhancing the nucleophilicity in the attack on the carbonyl group of propylene carbonate [12,33] . Moreover, this reaction is a reversible process, meaning that the molar ratio between the organic carbonate and glycerol plays a critical role in determining the equilibrium concentrations of reactants and products [13,34] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kondawar et al worked on glycerol transesterification preparing MgAl LDHs, pure or doped with Ca and La [112] (see Figure 6). While the study also interested the simple metal oxides, and CaO showed the highest activity, the formation of soluble calcium glycerate prevented its recovery and recyclability.…”
Section: Transesterification (Biodiesel Production)mentioning
confidence: 99%